Phenomenological study of texture zeros of fermion mass matrices in minimal extended seesaw mechanism. (October 2019) - Kumar, P; Patgiri, M
Abstract: We study the two-zero textures in M v 4 × 4 in minimal extended type-I seesaw (MES) mechanism with incorporating one extra gauge singlet field 'S'. M v 4 × 4 has (3×3)Dirac neutrino mass matrix MD, (3×3) right-handed Majorana mass matrix MR and (1×3) row matrix MS . For our study we consider 5 zeros in MD and 4 zeros in MR, (5+4) scheme, along with one-zero textures of MS to arrive at the two-zero textures of M v 4 × 4 . We find that out of 15 allowed two-zero textures, only 9 textures can be realized under (5+4) scheme. We also find that different textures of MD, MR and MS are related to each other through S3 permutation group which leads to only a few basic combinations of MD, MR and MS . We present all the combinations of MD, MR and MS and show their interconvertability nature due to S 3 symmetry between them.